Multiuser precoding techniques for a distributed broadband wireless system - Holakouei, Reza
In this paper we propose and asses multiuser linear precoding techniques for the downlink of distributed MIMO OFDM systems. We consider a distributed broadband wireless system where the base stations are transparently linked by optical fiber to a central unit. We further assume that both the distributed base stations and the user terminals are equipped with an antenna array. This architecture provides a high speed backhaul channel allowing an efficient joint multiuser multicell processing. The precoder is designed in two phases: first the intercell interference is removed by applying a block diagonalization algorithm. Then the system is further optimized by using a new power allocation algorithm, based on minimization of the sum of inverse signal-to-noise ratio (SNR−1) on each user terminal over the available subcarriers. The motivation to minimize the sum of SNR−1 instead of bit error rate is the fact that the first criterion achieves a closed-form solution, which is more interesting from practical point of view. The aim is to propose a practical distributed precoding technique to remove the intercell interference and improve the user’s fairness at the cell-edges. The performance of the proposed scheme is evaluated and compared with an iterative precoding scheme designed to minimize the bit error rate, extended to the proposed multiuser distributed scenario, considering typical pedestrian scenarios based on LTE specifications.